A multicenter randomized clinical trial of pharmacological vitamin B1 administration to critically ill patients who develop hypophosphatemia during enteral nutrition (The THIAMINE 4 HYPOPHOSPHATEMIA trial). Issue 8 (August 2021) - Deane, Adam M.; Jiang, Alice; Tascone, Brianna; Clancy, Annabelle; Finnis, Mark E.; Collie, Jake T.; Greaves, Ronda; Byrne, Kathleen M.; Fujii, Tomoko; Douglas, James S.; Nichol, Alistair; Udy, Andrew A.; et al.
Summary: Background: Hypophosphatemia may be a useful biomarker to identify thiamine deficiency in critically ill enterally-fed patients. The objective was to determine whether intravenous thiamine affects blood lactate, biochemical and clinical outcomes in this group. Method: This randomized clinical trial was conducted across 5 Intensive Care Units. Ninety critically ill adult patients with a serum phosphate ≤0.65 mmol/L within 72 h of commencing enteral nutrition were randomized to intravenous thiamine (200 mg every 12 h for up to 14 doses) or usual care (control). The primary outcome was blood lactate over time and data are median [IQR] unless specified. Results: Baseline variables were well balanced (thiamine: lactate 1.2 [1.0, 1.6] mmol/L, phosphate 0.56 [0.44, 0.64] mmol/L vs. control: lactate 1.0 [0.8, 1.3], phosphate 0.54 [0.44, 0.61]). Patients randomized to the intervention received a median of 11 [7.5, 13.5] doses for a total of 2200 [1500, 2700] mg of thiamine. Blood lactate over the entire 7 days of treatment was similar between groups (mean difference = −0.1 (95 % CI -0.2 to 0.1) mmol/L; P = 0.55). The percentage change from lactate pre-randomization to T = 24 h was not statistically different (thiamine: −32 (−39,  −26) vs. control: −24 (−31,  −16) percent, P = 0.09). Clinical outcomes were not statistically different (days of vasopressor administration: thiamine 2 [1, 4] vs. control 2 [0, 5.5] days; P = 0.37, and deaths 9 (21 %) vs. 5 (11 %); P = 0.25). Conclusions: In critically ill enterally-fed patients who developed hypophosphatemia, intravenous thiamine did not cause measurable differences in blood lactate or clinical outcomes. Trial registration: Australian and New Zealand Clinical Trials Registry (ACTRN12619000121167).